Tobacco TTG2 and ARF8 function concomitantly to control flower colouring by regulating anthocyanin synthesis genes. (23rd March 2017) - Li, P.; Chen, X.; Sun, F.; Dong, H.
Abstract: Recently we elucidated that tobacco TTG2 cooperates with ARF8 to regulate the vegetative growth and seed production. Here we show that TTG2 and ARF8 control flower colouring by regulating expression of ANS and DFR genes, which function in anthocyanin biosynthesis. Genetic modifications that substantially altered expression levels of the TTG2 gene and production quantities of TTG2 protein were correlated with flower development and colouring. Degrees of flower colour were increased by TTG2 overexpression but decreased through TTG2 silencing, in coincidence with high and low concentrations of anthocyanins in flowers. Of five genes involved in the anthocyanin biosynthesis pathway, only ANS and DFR were TTG2 ‐regulated and displayed enhancement and diminution of expression with TTG2 overexpression and silencing, respectively. The floral expression of ANS and DFR also needed a functional ARF8 gene, as ANS and DFR expression were attenuated by ARF8 silencing, which concomitantly diminished the role of TTG2 in anthocyanin production. While ARF8 required TTG2 to be expressed by itself and to regulate ANS and DFR expression, the concurrent presence of normally functional TTG2 and ARF8 was critical for floral production of anthocyanins and also for flower colouration. Our data suggest that TTG2 functions concomitantly with ARF8 to control degrees of flower colour by regulating expression of ANS and DFR, which are involved in the anthocyanin biosynthesis pathway. ARF8 depends on TTG2 to regulate floral expression of ANS and DFR with positive effects on anthocyanin production and flower colour.